(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Traumatic brain injury (TBI) is one of the most pressing issues in modern medicine due to its high incidence, severity of consequences, and significant socioeconomic losses. According to the World Health Organization, TBI causes death and disability in millions of people worldwide each year. Traumatic brain injuries account for up to 40% of all injuries, making them one of the leading causes of disability in young people.